Positioning of Logistics based on RFID and Integrated Sharing System - Qi Xu; Zheng Liu (Institute of Advanced Engineering and Science, 2013)
As logistics system becomes more complex, identifying and tracking a certain product or pallet in the whole process based on RFID in a real-time manner has played an important role. This study is focusing on identification, locating, tracking and dynamic management on logistics by using RFID technology. Firstly, an innovative scheme for the identification of an individual physical object through Web service is proposed. Then, an anti-collision framed slotted Aloha algorithm for the multiple tags simultaneously sensing is discussed. In addition, a selection sequence optimizing model via RFID technology is developed, and numerical analysis is made to explain the model. Finally, an RFID-based framework of dynamic logistics management system is put forward in order to realize logistics processes automatically verified and operation optimized. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3664